(untitled) (Revista Apotheke, 2024)
The following text is a reflection on the experience of creating the photographic catalog “Mapping.sensibles: photography in the Visual Arts course at URCA”. This project mapped the artistic production of students carried out during the workshops of the subjects “Photography I” and “Photography II”, throughout the first ten years of existence (2008-2018) of the Degree Course in Visual Arts at Universidade Regional do Cariri – URCA, and constituted a device to debate photography and studio practices as a way of thinking in the artistic field. To this end, I divided this article into “The catalogue”, “Mapping” and “Sensitive”.